2017
DOI: 10.1038/labinvest.2016.130
|View full text |Cite
|
Sign up to set email alerts
|

Early activated hepatic stellate cell-derived paracrine molecules modulate acute liver injury and regeneration

Abstract: The effects of paracrine action from early activated hepatic stellate cells (HSCs) on resident liver epithelium cells are not clear. Here, we investigated whether a systemic infusion of early activated HSC-derived paracrine factors (HSC-CM) would evoke an enhanced liver protective response in acetaminophen (APAP)-induced acute liver injury (ALI) in mice and explored the possible underlying mechanisms. The survival rate, liver injury, and liver regeneration were analyzed in mice with or without HSC-CM treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…PI3K/AKT is a classical signaling pathway that plays a key role in a veriety of physiological and pathological processes such as cell survival, growth, mogility, and apoptosis [49] and is known to inhibit in ammation and apoptosis by regulating multiple target proteins such as NF-κB and Bcl-2 family [50]. Previous studies have shown that IGF-1R/PI3K/AKT signaling pathway affect early liver regeneration and is involved in the development of APAP-induced ALF [51,52]. ERK is one of MAPK pathways and participates in the oxidative stress, cell apoptosis, and in ammation [53].…”
Section: Discussionmentioning
confidence: 99%
“…PI3K/AKT is a classical signaling pathway that plays a key role in a veriety of physiological and pathological processes such as cell survival, growth, mogility, and apoptosis [49] and is known to inhibit in ammation and apoptosis by regulating multiple target proteins such as NF-κB and Bcl-2 family [50]. Previous studies have shown that IGF-1R/PI3K/AKT signaling pathway affect early liver regeneration and is involved in the development of APAP-induced ALF [51,52]. ERK is one of MAPK pathways and participates in the oxidative stress, cell apoptosis, and in ammation [53].…”
Section: Discussionmentioning
confidence: 99%
“…The injection of CM without stem cells has been studied in various contexts but not in terms of vocal fold regeneration. As far as we know, this study is the first report on the injection of CM alone in the treatment of injured vocal folds in an animal model.…”
Section: Discussionmentioning
confidence: 99%
“…The paracrine effects of stem cells have been studied in various contexts. [36][37][38][39] However, the paracrine effects of stem cells in terms of conditioned medium have not been studied in the sphere of vocal fold regeneration. Further study is needed.…”
Section: Discussionmentioning
confidence: 99%